Erlotinib and gefitinib for treating non-small cell lung cancer that has progressed following prior chemotherapy (review of NICE technology appraisals 162 and 175) : a systematic review and economic evaluation /: a systematic review and economic evaluation. (June 2015) - Greenhalgh, J (Janette)
No abstract available